The Health Services White Paper : The Labour Party's policy
1944-09 1944 1940s 22 pages - 12 - The sale and purchase of practices. The White Paper naturally proposes that the sale and purchase of health centre practices should be abolished. Clearly, existing general practitioners who decide to go into health centres will have to be compensated for the loss of capital invested in the purchase of a practice which will no longer be saleable. What about all the other public practices of doctors not in health centres? The White Paper admits that there is a case for abolishing their sale and purchase, but says that this would raise great practical difficulties. The money involved in compensating the doctors would be small in relation to the total cost of the service. But once sale and purchase was abolished, this would mean that every public practice vacant would have to be advertised, and a candidate selected and appointed by a board. All young doctors, except those who were both wealthy and inefficient, would welcome the abolition of sale and purchase. Further, the setting up of health centres where doctors may start in general practice without having to raise purchase money will almost certainly greatly reduce the value of separate practice. So wise doctors outside health centres will certainly welcome the abolition of sale and purchase - with, of course, full compensation. The Labour Party is, therefore, strongly in favour of the abolition of sale and purchase of all public practices, with of course compensation for loss of capital investment. V. THE HOSPITAL AND SPECIALIST SERVICE EXAMINED In the second section of this report, it was shown why the Labour Party regards large health areas as an essential for an efficient hospital and specialist service; why the Party considers it essential that the controlling authorities of the new areas should be democratically responsible; and why also the voluntary hospitals must not be allowed to control their own State subsidies. It is now necessary to consider in greater detail:- The structure and functions of the new joint authorities The voluntary hospitals The municipal hospitals Planning a hospital service The specialist and consultant service The structure and functions of the new joint authorities. The new joint boards are to be composed of representatives of their constituent counties and county boroughs. In exceptional circumstances, where an authority is big enough to provide a complete service, for example in London, an existing major authority will take on the joint board's functions. The new authorities will have two main functions:- 1. They will take over all municipal hospitals, and clinics connected with the hospital and specialist service. Thus, they will control directly the municipal general, Poor Law, tuberculosis, fever, mental and other specialist hospitals, tuberculosis dispensaries, mental and cancer diagnostic clinics, and possibly V.D. clinics. 292/847/3/166